Behavioural and environmental risk factors associated with primary schoolchildren's overweight and obesity in urban Indonesia - Margarita de Vries Mecheva; Matthias Rieger; Robert Sparrow; Erfi Prafiantini; Rina Agustina (Cambridge University Press, 2023)
Abstract Objectives: To aid the design of nutrition interventions in low- and middle-income countries undergoing a nutrition transition, this study examined behavioural and environmental risk factors associated with childhood overweight and obesity in urban Indonesia. Design: Body height and weight of children were measured to determine BMI-for-age Z-scores and childhood overweight and obesity status. A self-administered parental survey measured socio-economic background, children's diet, physical activity, screen time and parental practices. Logistic and quantile regression models were used to assess the association between risk factors and the BMI-for-age Z-score distribution. Setting: Public primary schools in Central Jakarta, sampled at random. Participants: Children (n 1674) aged 6-13 years from 18 public primary schools. Results: Among the children, 31·0 % were overweight or obese. The prevalence of obesity was higher in boys (21·0 %) than in girls (12·0 %). Male sex and height (aOR = 1·67; 95 % CI 1·30, 2·14 and aOR = 1·16; 95 % CI 1·14, 1·18, respectively) increased the odds of being overweight or obese, while the odds reduced with every year of age (aOR = 0·43; 95 % CI 0·37, 0·50). Maternal education was positively associated with children's BMI at the median of the Z-score distribution (P = 0·026). Dietary and physical activity risk scores were not associated with children's BMI at any quantile. The obesogenic home food environment score was significantly and positively associated with the BMI-for-age Z-score at the 75th and 90th percentiles (P = 0·022 and 0·023, respectively). Conclusions: This study illustrated the demographic, behavioural and environmental risk factors for overweight and obesity among primary schoolchildren in a middle-income country. To foster healthy behaviours in primary schoolchildren, parents need to ensure a positive home food environment. Future sex-responsive interventions should involve both parents and children, promote healthy diets and physical activity and improve food environments in homes and schools.